COMMUNITY EMPOWERMENT WITH THE STUNTING KTP PROGRAM CAN INCREASE POSYANDU CADRES' KNOWLEDGE OF STUNTING PREVENTION: English - Karundeng, Jeni (Poltekkes Kemenkes Jayapura, 2024)
ABSTRACT Stunting is a global problem that is currently a concern for the world, especially in Indonesia. Stunting is a condition experienced by children during their toddler years, where the toddler has a height below average which is caused by inadequate nutritional intake. The causes of stunting in children in Indonesia are maternal education, maternal short stature, premature birth, baby's body length at birth, not providing exclusive breastfeeding for 6 months, and household socio-economic status. WHO says 3 out of 10 children under 5 years old experience stunting. Papua Province ranks third highest in national stunting. This happened because of an increase from 2021 of 29.5% to 34.6% in 2022.). Mimika Regency in 2022, stunting cases will be 33%. The aim of this community service is to assess whether community use of the KTP (Stunting Prevention Card) program can increase cadres' knowledge of Stunting prevention. The method used is 3-stage education, namely filling out a questionnaire beforehand, education with a booklet on how to play cards, playing cards to prevent stunting, evaluation with a post test. Results were measured using a pre-post test questionnaire and it was found that the level of community knowledge had increased. Keywords: Stunting, Community Empowerment, Stunting Prevention Card. ABSTRAK Stunting merupakan permasalahan global yang saat ini menjadi perhatian bagi dunia terlebih khusus di Indonesia. Stunting merupakan suatu kondisi yang dialami anak saat masa balita, dimana balita tersebut memiliki tanggi badan dibawah rata-rata yang diakibatkan oleh asupan gizi yang tidak adekuat. Penyebab stunting pada anak di Indonesia yaitu Pendidikan Ibu, Ibu bertubuh pendek, kelahiran premature, Panjang badan bayi saat lahir, tidak memberikan ASI eksklusif selama 6 bulan, dan status social-ekonomi rumah tangga. WHO menyebutkan 3 dari 10 anak di bawah umur 5 tahun mengalami stunting. Provinsi Papua menduduki urutan ketiga tertinggi stunting nasional. Hal ini terjadi karena adanya peningkatan dari tahun 2021 sebesar 29,5% menjadi 34,6% di tahun 2022.). Kabupaten Mimika tahun 2022 kasus stunting sebanyak 33%. Tujuan pengabdian masyarakat ini untuk menilai apakah pemanfaatan masyarakat dengan program KTP (Kartu Pencegahan Stunting) dapat meningkatkan pengetahuan kader terhadap pencegahan Stunting. Metode yang dilakukan dengan Edukasi 3 tahap yaitu pengisian kuisioner sebelum, edukasi dengan booklet cara bermain kartu, bermain kartu pencegah Stunting, evaluasi dengan post test. Hasil diukur menggunakan kuisioner pre post test dan didapatkan tingkat pengetahuan masyarakat meningkat. Kata Kunci: Stunting, Pemberdayaan Masyarakat, Kartu Pencegah Stunting,